Muscle spindles of the rat sternomastoid muscle - Walter Giuriati; Barbara Ravara; Andrea Porzionato; Giovanna Albertin; Carla Stecco; Veronica Macchi; Raffaele De Caro; Tiziana Martinello; Chiara Gomiero; Marco Patruno; Dario Coletti; Sandra Zampieri; et al. (European Journal of Translational Myology, 2018)
The sternomastoid (SM) muscle in rodents presents a peculiar distribution of fiber types with a steep gradient from the ventral, superficial, white portion to the dorsal, deep, red region, where muscle spindles are restricted. Cross section of the medial longitudinal third of the rat SM contains around 10,000 muscle fibers with a mean diameter of 51.28±12.62 (μm +/- SD). Transverse sections stained by Succinate Dehydrogenase (SDH) reaction clearly presents two distinct regions: the dorsal deep red portion encompassing a 40% cross section area contains a high percentage of packed SDH-positive muscle fibers, and the ventral superficial region which contains mainly SDH-negative muscle fibers. Indeed, the ventral superficial region of the rat SM muscle contains mainly fast 2B muscle fibers. These acidic ATPase pH 4.3-negative and SDH-negative 2B muscle fibers are the largest of the SM muscle, while the acidic ATPase pH 4.3-positive and SDH-positive Type 1 muscle fibers are the smallest. Here we show that in thin transverse cryosections only 2 or 3 muscle spindle are observed in the central part of the dorsal deep red portion of the SM muscle. Azan Mallory stained sections allow at the same time to count the spindles and to evaluate aging fibrosis of the skeletal muscle tissue. Though restricted in the muscle red region, SM spindles are embedded in perimysium, whose changes may influence their reflex activity. Our findings confirm that any comparisons of changes in number and percentage of muscle spindles and muscle fibers of the rat SM muscle will require morphometry of the whole muscle cross-section. Muscle biopsies of SM muscle from large mammals will only provide partial data on the size of the different types of muscle fibers biased by sampling. Nonetheless, histology of muscle tissue continue to provide practical and low-cost quantitative data to follow-up translational studies in rodents and beyond.